Characterization of Al-Containing Industrial Residues in the ESEE Region Supporting Circular Economy and the EU Green Deal - Fidanchevski, Emilija; Šter, Katarina; Mrak, Maruša; Rajacic, Milica; Koszo, Bence David; Ipavec, Andrej; Teran, Klemen; Žibret, Gorazd; Jovanov, Vojo; Aluloska, Nikolina Stamatovska; Loncnar, Mojca; Žibret, Lea; et al. (MDPI AG, 2024)
The increase in industrial waste generation presents a global problem that is a consequence of the needs of modern society. To achieve the goals of the EU Green Deal and to promote the concept of circular economy (CE), the valorization of industrial residues as secondary raw materials offers a pathway to economic, environmental, energetic, and social sustainability. In this respect, Al-containing industrial residues from alumina processing (red mud), thermal power plants (fly ash and bottom ash), and metallurgy (slag), as well as other industries, present a valuable mineral resource which can be considered as secondary raw materials (SRMs) with the potential to be used in construction, supporting the concept of circular economy. This paper focuses on the characterization of 19 secondary raw materials from the East South-East Europe (ESEE) region regarding their physical, chemical, mineralogical, and radiological characteristics. The goal is to provide a foundation for future innovations based on secondary raw materials, in alignment with the EU Green Deal and the principles of circular economy. The results showed that fly ash has the potential to be the best material among those analyzed to be used in the cement industry, mainly due to its favorable radiological and mineralogical properties. However, it is important to control the amount of free lime in the mixture, ensuring it remains below 10%. After evaluating secondary mineral raw materials for metal recovery, the results indicate that these materials are not viable sources for base metals or other technology-critical metals, such as REEs.
Keywords: Green Deal; Al-containing industrial residues; circular economy; fly ash; slag; red mud